2017
DOI: 10.1139/cgj-2016-0214
|View full text |Cite
|
Sign up to set email alerts
|

Brittle fracture of rock under combined tensile and compressive loading conditions

Abstract: The brittle fracture of rock with an angled crack under combined tensile and compressive loading conditions is studied using linear elastic fracture mechanics (LEFM). The modified maximum tangential stress criterion (MTSC) and the maximum shear stress criterion (MSSC) are used to check crack initiations in the tensile and shear modes, respectively. The effects of the friction coefficient of the crack surfaces and the nonsingular stresses (T stresses) on the crack initiation are studied for the cases of both lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…where σ θθ is the tangential stress at the flaw tip and σ c is the critical value of the tangential stress. The analysis results can well reflect the differences of fracture types of cracks under the action of tension and compression, and the results obtained are in good agreement with the experimental results, which makes it widely used in the theoretical research and practical engineering of rock failure [25][26][27][28].…”
Section: Theoretical Achievements Onsupporting
confidence: 69%
“…where σ θθ is the tangential stress at the flaw tip and σ c is the critical value of the tangential stress. The analysis results can well reflect the differences of fracture types of cracks under the action of tension and compression, and the results obtained are in good agreement with the experimental results, which makes it widely used in the theoretical research and practical engineering of rock failure [25][26][27][28].…”
Section: Theoretical Achievements Onsupporting
confidence: 69%
“…ere are many factors leading to the formation of different types of strain rock burst. However, no matter how complex its internal mechanism is, rock burst is mainly controlled by two factors, namely lithological conditions and stress field conditions [9][10][11][12][13]. It is found that the deep rock mass is mostly hard brittle rock mass, which generally meets the requirements of lithological conditions when rock burst occurs.…”
Section: Influencing Factors Of Tunnel Surrounding Rock Failurementioning
confidence: 99%
“…Therefore, for interface cracks in rock joints, a mode II fracture often occurs, which is different from traditional rock fracture mechanics, where a mode I fracture more commonly occurs and the initiation angle is about 70.5° [ 43 ].…”
Section: Initiation Of Interface Crackmentioning
confidence: 99%